KAJIAN GAYA BAHASA REPETISI DALAM LIRIK LAGU PADA BEBERAPA LAGU KARYA SECONDHAND SERENADE DALAM ALBUM A TWIST IN MY STORY : Indonesia - Sukendar; Lusi Susilawati (Nusantara Hasana Berdikari, 2021)
Understanding the language style of repetition on song lyrics is essential because some people prefer to listen to music more than poetry, especially in foreign languages. This research aims to identify the language style of repetition in the music, especially at several Secondhand Serenade songs on his album A Twist in My Story. The method that used in this research is three steps, which include data preparation techniques, data analysis techniques, and data presentation techniques. The first step on preparation data is using the “simak” method and “catat” method. After that, the data analysis using the intralingual equivalent method and the last step, using the informal procedure. This study revealed some styles of repetition that identified as twenty-one repetitions: two anadiplosis repetitions, six anaphora repetitions, two epalenepsis repetitions, three epistrophe repetitions, and four epizeukis repetitions, and four mesodiplosis repetitions. On the other hand, some types of repetitions aren't identified or couldn't be found in this research, including tautotes repetitions and simploke repetitions.